Molecular phylogenetics and morphological variation reveal recent speciation in freshwater mussels of the genera Arcidens and Arkansia (Bivalvia: Unionidae). (4th June 2014) - Inoue, Kentaro; McQueen, Alyssa L.; Harris, John L.; Berg, David J.
<x xml:space="preserve">Abstract</x> Intra‐ and interspecific morphological variation due to both phenotypic plasticity and evolutionary convergence hinder the work of taxonomists and lead to over‐ and underestimates of species richness. Nevertheless, most species on Earth are recognized solely based on morphological characters. We used molecular phylogenetic and morphometric techniques to examine two freshwater mussel species. One is common and widespread, while the other is imperiled and endemic to the Interior Highlands of the USA. Phylogenetic and molecular clock analyses revealed that divergence of Arcidens confragosus and Arkansia wheeleri is small and relatively recent. Divergence in these and other taxa is probably due to isolation of streams in the Interior Highlands. Morphometric analyses showed distinct shell shapes using traditional morphometrics, but not through geometric morphometrics. Outlined shell shapes are indistinguishable; geometric morphometrics could not capture a three‐dimensional component. Our analyses support the validity of these two species as congeners, with the nomen Arcidens (Simpson 1900) having priority. Because shell morphologies are both heritable and environmentally determined, our study emphasizes the importance of considering both molecular and morphometric analyses for identification of freshwater molluscs of conservation concern. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 535–545.